Diagnosis and treatment of descending optic neuritis developed as a manifestation of local viral encephalitis (a clinical case) - N.V. Korsakova; E.I. Korsakova (РМЖ "Клиническая офтальмология")
N.V. Korsakova1,2, E.I. Korsakova3 1I.N. Ulianov Chuvash State University, Cheboksary, Russian Federation 2Cheboksary Branch of the S. Fyodorov Eye Microsurgery Federal State Institution, Cheboksary, Russian Federation 3Pirogov Russian National Research Medical University, Moscow, Russian Federation It is well known that the incidence of encephalitis and optic neuritis is relatively high worldwide. Moreover, it is associated with high mortality and disability rates. At the same time, in 45–75% of cases, optic neuritis affects the central nervous system causing its disorders of various severity. Unfortunately, for practicing ophthalmologists and neurologists it is difficult to find a relationship between optical neuritis and inflammation of the brain tissue (especially when it is limited by a certain part of the brain) which underlies the diagnosis of opticoencephalitis. In this context, an ophthalmologist who can use methods of ophthalmological diagnostics will play a more important role. The ophthalmologist will be able to arrive at a topical diagnosis and localize a level of the brain tissue lesion, which is essential for determining the disease but cannot be done by neurologist. This publication presents our own clinical observation describing the specific aspects of diagnosis and treatment of descending optic neuritis co-occurring with viral inflammation of the brain tissue. The article provides analysis of the clinical signs which both impeded and facilitated the process of making the accurate diagnosis. It should be recognized that during the process of opticoencephalitis development, its ophthalmic manifestations for a long time will not only remain a single sign of this focal neurological disorder, but will require timely initiation of etiotropic drugs, using the appropriate routes of administration, doses, and duration of treatment. Thus, it is important to be aware and prepared for detecting viral encephalitis (opticoencephalitis) even at the slightest suspicion for a descending pathway of the diagnosed inflammation of the eye tissues. Keywords: optical neuritis, encephalitis, herpes virus, markers, antibodies, vesicles, ophthalmoscopy, perimetry. For citation: Korsakova N.V., Korsakova E.I. Diagnosis and treatment of descending optic neuritis developed as a manifestation of local viral encephalitis (a clinical case). Russian Journal of Clinical Ophthalmology. 2022;22(4):273–278 (in Russ.). DOI: 10.32364/2311-7729-2022-22-4-273-278.